Study and Application of Rice Seedling Film with Bast Fiber in China - Zhong Yi Sun; Qing Hua Kang; Yu Fu Wang; Ping Yan; Xi Xia Song; Cai Sheng Qiu; Hong Da Wu; Dan Dan Yao; Zhen Hua Xu; Wei Dong Jiang; Hai Ying Liu; Bei Ping Zhao; et al. (Journal of Natural Fibers, 2025)
There are quite a number of bast fiber crops, and their uses are also very extensive. Bast fiber film is just one of their many applications. Bast fiber film can not only be used to cover the soil where crops are planted for heat and moisture preservation but also can be used for rice seedling cultivation. Therefore, China has specifically developed the bast fiber seedling film for rice seedling cultivation, which has effectively solved the problem that rice seedlings cultivated by seedling trays are prone to scattering during mechanical transplanting and has achieved a great success. It significantly improves the quality and efficiency of mechanical transplanting operations, and improving rice yieldfinally. This paper aims to summarize the development of bast fiber film in China and its study and application in rice seedling cultivation, explore the application and future development direction of bast fiber film in rice seedling cultivation, and assist in expanding the uses of bast fiber and in the development and application of the rice seedling cultivation technology with bast fiber seedling film in the world.